2008
DOI: 10.1186/1471-2407-8-266
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of tumor suppressor miR-34 inhibits human p53-mutant gastric cancer tumorspheres

Abstract: Background: MicroRNAs (miRNAs), some of which function as oncogenes or tumor suppressor genes, are involved in carcinogenesis via regulating cell proliferation and/or cell death. MicroRNA miR-34 was recently found to be a direct target of p53, functioning downstream of the p53 pathway as a tumor suppressor. miR-34 targets Notch, HMGA2, and Bcl-2, genes involved in the self-renewal and survival of cancer stem cells. The role of miR-34 in gastric cancer has not been reported previously. In this study, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
266
2
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(288 citation statements)
references
References 51 publications
12
266
2
4
Order By: Relevance
“…Both forms of the lymphomas have definitive clinicopathological entities characterized by their unique histological and clinical features [1][2][3]. Research showed that miR-34a regulation of B-cell development and apoptosis were possibly related to the tumor suppressor p53, oncogenic protein BCL2, and FOXP1 [10][11][12][13][14][15][16][17][18]. In this study, we assessed corelations of miR-34a level and the expression of the B-cell differentiation-and apoptosisrelated proteins FOXP1, p53, and BCL2 with the clinicopathological features and survival of gastric MALT lymphoma and DLBCL.…”
Section: Follow-up and Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…Both forms of the lymphomas have definitive clinicopathological entities characterized by their unique histological and clinical features [1][2][3]. Research showed that miR-34a regulation of B-cell development and apoptosis were possibly related to the tumor suppressor p53, oncogenic protein BCL2, and FOXP1 [10][11][12][13][14][15][16][17][18]. In this study, we assessed corelations of miR-34a level and the expression of the B-cell differentiation-and apoptosisrelated proteins FOXP1, p53, and BCL2 with the clinicopathological features and survival of gastric MALT lymphoma and DLBCL.…”
Section: Follow-up and Survivalmentioning
confidence: 99%
“…The same studies showed that BCL2 was targeted by miR-34a, and that there was a direct interaction between miR-34a and the tumor suppressor p53 and the oncogenic protein BCL2. This interaction was shown to increase the survival of miR-34a-expressing pro-B cells but did not significantly promote their differentiation [10,11,13,14]. Other studies have shown that the forkhead box protein 1 (FOXP1) is involved in B-cell differentiation and survival [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When introduced into cancer cells, miR34a induces cell-cycle arrest (6), senescence (7), and apoptosis (7). The miRNA also inhibits cancer stem cell development (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%